Cost-Effectiveness of the Hepatitis C Self-Management Program. (February 2017) - Groessl, Erik J.; Sklar, Marisa; Laurent, Diana D.; Lorig, Kate; Ganiats, Theodore G.; Ho, Samuel B.
Background. Despite the emergence of new hepatitis C virus (HCV) antiviral medications, many people with chronic HCV know little about their disease, are at risk for transmitting HCV to others, and/or are not considered good treatment candidates. Self-management interventions can educate HCV-infected persons, improve their quality of life, and prepare them for treatment. Purpose. A cost-effectiveness analysis of the HCV Self-Management Program is presented. Method. Effectiveness data in quality-adjusted life years (QALYs) were derived from the previously published prospective, randomized controlled trial ( n = 134). Health care utilization was abstracted from medical records in 2011 for the 12 months before and after study enrollment. Intervention costs were tracked from the payer's perspective and combined with health care costs. Sensitivity analyses were used to examine assumptions. Data were analyzed in 2014. Results. Estimated intervention costs including organizational overhead were $1, 760 per 6-week workshop, or $229/person. Health care costs were $815 lower/person for self-management participants, resulting in a cost savings of $586/person. Self-management participants had an average net gain of 0.02975 QALYs after 1 year. When removing inpatient substance use treatment days from analyses, costs were similar between groups, producing an incremental cost-effectiveness ratio of $6, 218/QALY. Sensitivity analyses showed that the results and conclusions change little when assumptions were varied. Conclusions. When compared to information-only, the HCV Self-Management Program led to more QALYs and cost savings in the randomized controlled trial. Independent of health care costs, the intervention is low-cost and educates HCV-infected individuals about antiviral treatment and avoiding viral transmission. Low-cost interventions that can enhance the outcomes derived from expensive antiviral treatments should be studied further.